Arbitration Reform in Kazakhstan: The History and the Current Developments - KONUSSOVA, Venera T.; TASTANOVA, Malika M.; YELEUSSIZOVA, Indira K.; TLEMBAEVA, Zhanna U. (Journal of Advanced Research in Law and Economics; Vol 7 No 2 (2016): JARLE, Volume VII, Issue 2(16), Spring 2016, 2016)
This article attempts to highlight the most important milestones of the historical development of commercial arbitration in Kazakhstan in order to show the way, which has led to the current reform. The authors tried to give critical analyses of each step of the commercial arbitration evolution and contemplate on the plausible effect of the new Bill on arbitration. The analysis of commercial arbitration development is divided into several steps based on some historical predispositions such as changes in political regime of the country and some impactful developments in the legislative regulation of arbitration, which took place after getting state independence. Thus, in the frames of such analysis, the authors found that regulation of the commercial arbitration on each step of its development reflects the main trends in the economic policy of the country.